Surgical management of intraventricular hemorrhage and posthemorrhagic hydrocephalus in premature infants - Meng-Fai Kuo (Biomedical Journal, 2020)
Perinatal intraventricular hemorrhage (IVH) with or without development of posthemorrhagic hydrocephalus (PHH) in premature neonates may lead to severe neurological disability. Although the percentage of preterm infants developing IVH has been greatly reduced in the last three decades, increased survival of these very immature infants has meant that large IVH with subsequent PHH is still a serious unsolved problem. Early cerebrospinal fluid diversion as a temporizing measure or a permanent shunt is the treatment of choice. This review summarizes the surgical modalities, techniques, and their complications in the management of IVH and PHH in premature infants. Though there is no level-one evidence to support the superiority of any of the currently available managements in the initial treatment of PHH over others, this review aims to provide pediatric neurosurgeons a comprehensive understanding of the pros and cons of various surgical treatment modalities, focusing on the temporizing measures before the infants is heavy enough to undergo ventriculoperitoneal shunt insertion. Based on the patient's condition, the facility and man power of the institution with minimal complication rate, the pediatric neurosurgeons may choose the best initial approach for the management of IVH and PHH in premature infants.